Markers and Patterns of Organizational Resilience for Risk Analysis. Issue 19 (2016) - De Galizia, A.; Simon, C.; Weber, P.; Iung, B.; Duval, C.; Serdet, E.
Abstract: In recent years, the concept of resilience has been introduced in risk analysis and some approaches have been proposed as an alternative (or a complement) to the conventional safety assessment for sociotechnical systems. In that way, Integrated Risk Analysis (IRA) has been developed at EDF to treat different risk causalities linking human, organizational, technical and environmental factors in a unified framework using performance shaping factors (PSF). However, research is still needed to address the issues relating to the modelling of resilience when considering organizational influences on human activities. Thus, this paper aims contributing at the definition and derivation of resilient markers and, consequently, to consider both resilient and pathogenic organizational patterns in a unified risk model. The risk model is initially proposed as a fourth generation method of risk analysis based on probabilistic graphical modelling of causal mechanisms. The model is proposed for safety assessment of technical systems integrating human, environmental and organizational factors. Finally, the feasibility of our proposals is shown on an illustrative case of Integrated Risk Analysis (IRA).